Характеристика основних факторів поширення расизму та ксенофобії як фонових для злочинності явищ в Україні - Прібиткова, Н. О.; Pribytkova, N. O.; Наталія Прібиткова (Право і Безпека. - 2016. - № 2 (61). - С. 88–93, 2016)
У рамках висвітлення проблем детермінації расизму та ксенофобії як фонових для злочинності явищ в Україні розглянуто поняття расизму та ксенофобії та охарактеризовано основні фактори їх поширення. Досліджено стан поширеності расизму та ксенофобії в Україні.

In the frames of highlighting the problem of determination of racism and xenophobia as background phenomena for the crime in Ukraine the author has considered the notion of racism and xenophobia and has characterized the main factors of their spreading. The state of the prevalence of racism and xenophobia in Ukraine has been studied. It has been noted that the spread of racism and xenophobia is a testament to the existing social tensions, the main source of which is the dissatisfaction of the indigenous population to a particular locality to their socio-economic status, feeling the threat of cultural diffusion, increased competition in the labor market and other dimensions of social extent. Studying the factors of racism and xenophobia as background phenomena for the crime should be arranged for the general logic of criminological research, in particular to divide them on social and economic, cultural and psychological, political, legal, organizational and managerial. Socioeconomic factors of the spread of racism and xenophobia are though nonspecific factors, but those that are among the most powerful in terms of determining the general features of sociodynamics. Being in the unity with the social and economic factors, cultural and psychological ones exacerbate deformation processes in various forms of social consciousness, especially in the moral, political and legal awareness. The level of ethnic bias in Ukraine under the influence of a number of economic, social and political factors has a stable growth tendency. Further exacerbation of determination complex of racism and xenophobia forms a cascade of risks of criminogenic nature, that ahead of European integration of Ukraine and opposition to external aggression are able to acquire the level of threats to national security, to serve as the basis for the use of manipulative practices of a criminal and political nature.

В рамках освящения проблем детерминации расизма и ксенофобии как фоновых для преступности явлений в Украине рассмотрены понятия расизма и ксенофобии и охарактеризованы основные факторы распространения. Исследовано состояние распространённости расизма и ксенофобии в Украине.
Characteristics Of The Main Factors Of Spreading Racism And Xenophobia As Background Phenomena For The Crime In Ukraine
Характеристика основных факторов распространения расизма и ксенофобии как фоновых для преступности явлений в Украине
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; расизм; ксенофобія; злочинність; фонове для злочинності явище; фактори поширення расизму та ксенофобії; racism; xenophobia; crime; background phenomena; factors of spreading racism and xenophobia; ксенофобия; преступность; фоновые явления; фоновое для преступности явление; фонові явища; факторы распространения расизма и ксенофобии